The origins of industrial capitalism in India : business strategies and the working classes in Bombay, 1900-1940 - Chandavarkar, Rajnarayan (Cambridge South Asian studies, 1994)
In The Origins of Industrial Capitalism in India, Rajnarayan Chandavarkar presents the first comprehensive study of the relationship between labour and capital in India's economic development in the early twentieth century. Hitherto the working class has been largely overlooked in Indian history. By focussing upon the economy of labour in Bombay city from 1900 to 1940, Dr Chandavarkar makes a major contribution to redressing this imbalance.